Keserasian antar Bunyi dalam Konsep Fonologi Bahasa Arab al-Khalil Ibn Ahmad al-Farahidi - Akhmad Saehudin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
This article is focus on the Arabic phonological concept wich was proposed by al-khalil Ibn Ahmad al-Farahidi in order to introduce the fluency of pronouncing Arabic words. According to al-farahidi the fluency of prononcing the Arabic words are formed through the grammatically arranged sentences, wich are built through the correct words. Mean while correct words are formed trough the exact placement of the sounds. This article will expose al-Farahidi's efforts in identifying the harmonious sound of Arabic words which finally form fluency of pronouncing the words.